The participation myth. Issue 1 (2nd January 2017) - Jancovich, Leila
Abstract : Policy rhetoric around strategies to and the value of increasing participation in the arts has been well documented internationally over more than a decade. But in the UK, which is the focus for this article, targets to increase participation have been consistently missed and there remains a direct correlation between those taking part in cultural activity and their socio-economic status. The starting point for this article is to examine the barriers to increasing participation in the arts and question the way that such policy has been implemented within the English context, which may have relevance for policy-making in other countries. What is demonstrated is that policy implementation is influenced by vested interest of those in receipt of funding and that a narrow range of voices, from a powerful cultural elite, are involved in the decision-making in the arts. The article makes a case for widening the range of voices heard in decision-making in order to support both artistic practice and public engagement.